Inverse problem of simultaneous determination of two coefficients in a parabolic equation - Ivanchov, N. I. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish conditions for the unique existence of a solution of the inverse problem of simultaneous determination of two unknown coefficients in a parabolic equation. One of these coefficients is the leading coefficient that depends on time, and the other coefficient depends on a space variable.